Long-Chain Polysaturated Fatty Acid in Atrial Fibrillation–Associated Stroke: Lipidomic-GWAS Study - Jung, Youngae; Kim, Beomsu; Kim, Chi Kyung; Won, Hong-Hee; Chae, Su-Hyun; Oh, Kyungmi; Shin, Min-Jeong; Hwang, Geum-Sook; Seo, Woo-Keun (Thrombosis and Haemostasis, 2025)
This study aimed to explore the relationship between lipidomic domains, particularly free fatty acids (FFAs), and the presence of atrial fibrillation (AF) in patients with acute stroke, and to identify mechanisms of AF-associated stroke through genetic studies.A total of 483 stroke patients without AF (n = 391) and with AF (n = 92) were selected from a prospectively collected stroke registry. Lipidomic profiling was conducted, and the lipid components associated with AF were explored using fold-change analyses and clustering. Genotyping was conducted through trait comparison. Colocalization was also performed.Among the lipidomic domains, the free fatty acid (FFA) class was positively associated with AF. Long-chain fatty acids with 14 to 24 carbons and unsaturated FFAs distinguished AF. Clustering analysis based on FFAs revealed differences in AF proportion across groups. Genome-wide association study (GWAS) identified two loci associated with clustered groups of FFA metabolites: near MIR548F3 associated with FFA 20:1, FFA 20:2, FFA 22:5, and FFA 22:6; and near RPL37A associated with FFA 22:5 and FFA 22:6. These loci were associated with increased fibrinogen levels. In the GWAS for the FFA metabolite, quantitative trial locus analysis, loci near rs28456 and rs3770088, and FFA 20:4-QTLs were co-localized with the eQTLs of FADS2, a gene involved in the peroxisome proliferator-activated receptor gamma-related signaling pathway, in the whole blood, left ventricle, and atrial appendage tissue.Elevated FFA levels, especially those of long-chain unsaturated FFAs, are strongly associated with AF-associated stroke. This relationship is regulated by the peroxisome proliferator-activated receptor (PPAR) gamma-related signaling pathway.
Keywords: atrial fibrillation; stroke; lipidomics; genome-wide association study; free fatty acids; peroxisome proliferator-activated receptor gamma